2020
DOI: 10.1101/2020.11.18.20231688
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cov-MS: a community-based template assay for clinical MS-based protein detection in SARS-CoV-2 patients

Abstract: Rising population density and global mobility are among the reasons why pathogens such as SARS-CoV-2, the virus that causes COVID-19, spread so rapidly across the globe. The policy response to such pandemics will always have to include accurate monitoring of the spread, as this provides one of the few alternatives to total lockdown. However, COVID-19 diagnosis is currently performed almost exclusively by Reverse Transcription Polymerase Chain Reaction (RT-PCR). Although this is efficient, automatable and accep… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 45 publications
2
23
0
Order By: Relevance
“…It has been demonstrated that 10 genomes, i.e. DNA plasmids, 11 can be detected in a volume of 10 µl with cycle times (ct) of 38 in RT-qPCR experiments. A RT-qPCR detection with a ct value of 18 would require the presence of 10,485,760 genome equivalents in 10 µl.…”
Section: Optimization Of Sample Preparation Improving Our Sample Preparation Protocol Included Sample Collection Sample Homogeneity Samplmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been demonstrated that 10 genomes, i.e. DNA plasmids, 11 can be detected in a volume of 10 µl with cycle times (ct) of 38 in RT-qPCR experiments. A RT-qPCR detection with a ct value of 18 would require the presence of 10,485,760 genome equivalents in 10 µl.…”
Section: Optimization Of Sample Preparation Improving Our Sample Preparation Protocol Included Sample Collection Sample Homogeneity Samplmentioning
confidence: 99%
“…Calculations with 300 molecules of nucleoprotein per SARS-CoV-2 virus particle 11 result in a nucleoprotein concentration of ~ 520 amol/µl, corresponding to a ct value of 18. 11 In our experiments, we used 100 µl of saliva and generated 70 µl of sample solution for LC/MS analysis. Under these conditions, the concentration of SARS-CoV-2 nucleoprotein peptides would be 743 amol/µl, which is above our estimated LOD/LOQ of ~ 500 amol/µl (see above).…”
Section: Optimization Of Sample Preparation Improving Our Sample Preparation Protocol Included Sample Collection Sample Homogeneity Samplmentioning
confidence: 99%
See 3 more Smart Citations